Oral Multiple Sclerosis Drugs Inhibit the In vitro Growth of Epsilon Toxin Producing Gut Bacterium, Clostridium perfringens - Rumah, Kareem R.; Vartanian, Timothy K.; Fischetti, Vincent A. (Frontiers in Cellular and Infection Microbiology, 2017)
There are currently three oral medications approved for the treatment of multiple sclerosis (MS). Two of these medications, Fingolimod, and Teriflunomide, are considered to be anti-inflammatory agents, while dimethyl fumarate (DMF) is thought to trigger a robust antioxidant response, protecting vulnerable cells during an MS attack. We previously proposed that epsilon toxin from the gut bacterium, Clostridium perfringens, may initiate newly forming MS lesions due to its tropism for blood-brain barrier (BBB) vasculature and central nervous system myelin. Because gut microbiota will be exposed to these oral therapies prior to systemic absorption, we sought to determine if these compounds affect C. perfringens growth in vitro. Here we show that Fingolimod, Teriflunomide, and DMF indeed inhibit C. perfringens growth. Furthermore, several compounds similar to DMF in chemical structure, namely α, β unsaturated carbonyls, also known as Michael acceptors, inhibit C. perfringens. Sphingosine, a Fingolimod homolog with known antibacterial properties, proved to be a potent C. perfringens inhibitor with a Minimal Inhibitory Concentration similar to that of Fingolimod. These findings suggest that currently approved oral MS therapies and structurally related compounds possess antibacterial properties that may alter the gut microbiota. Moreover, inhibition of C. perfringens growth and resulting blockade of epsilon toxin production may contribute to the clinical efficacy of these disease-modifying drugs.